Correction: Exposure to mass media chronic health campaign messages and the uptake of non-communicable disease screening in Ghana. - Irenius Konkor; Elijah Bisung; Ophelia Soliku; Martin Ayanore; Vincent Kuuire (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0302942.].